Hypercalciuria is an important cause of urinary tract infection in children - Abdullah, Muhsina; Hossain, Md Shahadat; Khan, Md Anwar Hossain; Uddin, Md Nasir; Ishrat, Rumana; Jahan, Nur Wa Bushra; Rahman, Md Mahabubr; Alam, Mohammed Morshed (Bangladesh Medical Journal, 2014)
Urinary tract infection is a common disease in paediatric practice and an important cause of morbidity. Recurrence is frequent and occurs in approximately 40% in female and 32% in male. The association of hypercalciuria and UTI has been pointed out by several authors from different countries during the last 7-10 years. This prospective case control study was designed to evaluate the association between hypercalciuria and UTI in children in the department of Biochemistry, DMC and National Institute of Kidney Diseases and Urology (NIKDU) from July 2007- June 2008 on 30 cases of diagnosed UTI and 40 age-sex matched apparently healthy control. Blood samples of all study subjects were analyzed for serum total calcium concentration to exclude hyper or hypocalcaemia. Random urine samples were analyzed for urinary calcium creatinine ratio to screen hypercalciuria. In this study, urinary calcium creatinine ratio ? 0.20 was considered as hypercalciuria. Hypercalciuria were reported in 46.7% cases whereas only in 20.0% controls which was significantly higher in cases (p<0.05). Among the cases, 76.7% had recurrent UTI and 23.3% had first time UTI. Hypercalciuria were reported in 52.2% cases with recurrent UTI and only in 28.6% cases with first time UTI. Hypercalciuria in cases with recurrent UTI were also found significantly higher compared to controls (p<0.05). It was therefore concluded that hypercalciuria is associated with UTI and is an important cause of UTI in children. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21369 Bangladesh Med J. 2014 January; 43 (1): 9-12